2023
DOI: 10.1007/s00259-023-06272-7
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison of different classes of FAP radioligands designed to increase tumor residence time: monomer, dimer, albumin binders, and small molecules vs peptides

Abstract: Purpose Fibroblast activation protein-α (FAP)-targeting radioligands have recently demonstrated high diagnostic potential. However, their therapeutic value is impaired by the short tumor residence time. Several strategies have been tested to overcome this limitation, but a head-to-head comparison has never been done. With the aim to identify strengths and limitations of the suggested strategies, we compared the monomer FAPI-46 versus (a) its dimer (FAPI-46-F1D), (b) two albumin binders conjugates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…18,21,28,35,36 In a head-to-head comparison, dimerization of FAPI has emerged as a highly promising strategy for enhancing tumor uptake. 37 An overview presents the current status of FAP-targeted dimers in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,21,28,35,36 In a head-to-head comparison, dimerization of FAPI has emerged as a highly promising strategy for enhancing tumor uptake. 37 An overview presents the current status of FAP-targeted dimers in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, the ligand’s interaction with a single receptor significantly boosts its localized concentration near the receptor, which consequently intensifies the binding avidity. Enhancements in binding avidity and a decreased receptor off-rate collectively contribute to a significant elevation in tumor uptake, thereby underscoring the pivotal role of dimerization interactions in optimizing the efficacy of targeted therapeutic agents. ,,,, In a head-to-head comparison, dimerization of FAPI has emerged as a highly promising strategy for enhancing tumor uptake . An overview presents the current status of FAP-targeted dimers in Table .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to FAP, BR also represents a broad-spectrum target, presenting advantages for application in tumors where cancer cells exhibit low or no FAP expression. Preclinical studies often utilize artificially transfected tumor cells (HT1080-FAP) or tumor cells with high FAP expression like U87-MG, , which may not accurately reflect the clinical scenario where most cancer cells within tumors exhibit either low or no expression of FAP. , This mismatch can reduce the sensitivity of radioligands, particularly in cases where the TME has not formed or FAP expression on CAFs is not elevated . In this study, A549 cells were employed to address this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed that the hydrophilic properties of the transthyretin binder (TB-01) enabled to maintain the hydrophilic properties of the resultant radioligand visible by comparable logD values of [ 177 Lu]Lu-PSMA-TB-01 (logD: −3.4) and [ 177 Lu]Lu-PSMA-617 (logD: −4.4 [14]), while the use of the p-iodophenyl and p-tolyl entities ([ 177 Lu]Lu-PSMA-ALB-53/56, logD values: −2.7 to −2.9) commonly enhanced the lipophilicity of the resultant radioligands. The increased lipophilicity upon the modification with an albumin binder has also been observed using other tumor targeting agents, which resulted in higher background activity [33,34]. Hydrophilic properties of radiopharmaceuticals are commonly desirable to favor renal excretion and prevent background activity in the liver and intestinal tract.…”
Section: Discussionmentioning
confidence: 99%